(untitled) (Eureka Journal of Computing Science & Digital Innovation, 2026)
Early identification of chronic disease risks is a critical challenge in modern healthcare systems due to increasing patient loads and the complexity of clinical data. Medical informatics offers effective tools for integrating, processing, and analyzing health data to support preventive decision-making. The objective of this study is to develop an information system designed for the early risk assessment of chronic diseases based on the analysis of clinical and demographic data.